Application of DCC-GARCH Model for Analysis of Interrelations Among Capital Markets of Poland, Czech Republic and Germany - Marek Zinecker; Adam P. Balcerzak; Marcin Faldzinski; Michal Bernad Pietrzak; Tomáš Meluzin (Institute of Economic Research (IER), 2016)
The phenomenon of growing capital market linkages is a significant exogenous factor affecting the effectiveness of national economic policies and risk management processes in enterprises. As a result the identification of interdependencies among capital markets is important both from the macro and microeconomic perspective. In this context the main aim of this article is to examine the relations among capital markets of Poland, Czech Republic and Germany. In the research DCC-GARCH model with the t-student conditional distribution was applied. The analysis was conducted for the years 1997-2015. The research findings confirmed significant interdependencies among analysed capital markets, which were evaluated here by conditional correlations.
Keywords: G15; C58; 330; interdependences among capital markets; conditional variance and correlations; DCC-GARCH model